Analisis Systematic Literature Review Tentang Strategi Pengembangan Bisnis UMKM Melalui Digitalisasi Proses Bisnis - Saadatul Husna; Jeni Susyanti (PT PUBLIKASI INSPIRASI INDONESIA, 2024)
This research was conducted using a systematic literature review to identify and describe research findings regarding MSME business development strategies through digitalization of business processes. This research is aimed at adding to the incomplete literature research studies on the research topic. The method used is literature review analysis of 30 nationally indexed research journals sourced from Google Scholar from 2020-2024. The results of the analysis carried out showed that many business strategies in MSMEs were carried out by academics by carrying out community service activities regarding digital marketing as the mainstream, followed by the use of social chat, digital financial literacy, social media and marketplaces. The use of SWOT analysis strategies, Technology Readiness Index (TRI) strategies, business feasibility strategies and incubation and collaboration strategies where the role of various sectors, especially the government, in making policies greatly determines the development of MSME businesses.